2023
DOI: 10.1002/edm2.418
|View full text |Cite
|
Sign up to set email alerts
|

Effect of circulating ceramides on adiposity and insulin resistance in patients with type 2 diabetes: An observational cross‐sectional study

Abstract: Introduction Insulin resistance (IR) is one of the common chronic metabolic disorders in Africa and elsewhere. Accumulation of lipids in the body may be due to an imbalance in the metabolism of lipids, glucose and proteins. Ceramides are a sphingolipid class of lipids that are biologically active and vital in the production of more complex lipids. Circulating ceramides are thought to have a role in the development of obesity‐related IR, although the precise involvement remains unclear. Aim To investigate the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Ceramide, a type of fat in cells, has been linked to lipid-mediated skeletal muscle IR. 97–99 Research has shown that individuals with T2DM have higher blood levels of ceramide, 100 which is associated with IR, insulin sensitivity, and cardiovascular risk. 101 This is consistent with a previous study showing obese and diabetic patients have higher levels of ceramide in their muscles.…”
Section: Resultsmentioning
confidence: 99%
“…Ceramide, a type of fat in cells, has been linked to lipid-mediated skeletal muscle IR. 97–99 Research has shown that individuals with T2DM have higher blood levels of ceramide, 100 which is associated with IR, insulin sensitivity, and cardiovascular risk. 101 This is consistent with a previous study showing obese and diabetic patients have higher levels of ceramide in their muscles.…”
Section: Resultsmentioning
confidence: 99%
“…The body fat percentage was calculated using the subsequent formula. The formula applied to men was 0.567 × WC + 0.101 × age (years) – 31.8, while for females, the formula was 0.438 × WC + 0.221 × age (years) – 9.4 [ 16 , 17 ]. After 20 min of rest, the participant's blood pressure (BP) was measured in the left arm using an automated BP monitor (OMRON Healthcare Company Limited, Kyoto, Japan) while maintaining a seated position.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, studies have already shown that incubations of various insulin-responsive cells with exogenous short-chain ceramides (C2-ceramides) lead to insulin resistance [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ], suggesting that an extracellular supply of ceramides may also be deleterious to the cell and may play an additive role to that of de novo produced ceramides. Thus, although increased intracellular ceramide concentrations have been associated with the onset and the development of metabolic diseases, this may not be exclusively due to intracellular de novo ceramide synthesis since several other studies have also demonstrated strong correlations between elevated circulating ceramides and insulin resistance and T2D [ 43 , 72 , 73 , 74 , 75 , 75 , 76 , 77 , 78 ].…”
Section: Ceramides and Lipoproteinsmentioning
confidence: 99%